2017
DOI: 10.1002/jcp.26059
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule actin crosslinking factor 1 promotes osteoblast differentiation by promoting β‐catenin/TCF1/Runx2 signaling axis

Abstract: Osteoblast differentiation is a multistep process delicately regulated by many factors, including cytoskeletal dynamics and signaling pathways. Microtubule actin crosslinking factor 1 (MACF1), a key cytoskeletal linker, has been shown to play key roles in signal transduction and in diverse cellular processes; however, its role in regulating osteoblast differentiation is still needed to be elucidated. To further uncover the functions and mechanisms of action of MACF1 in osteoblast differentiation, we examined e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
40
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 40 publications
5
40
0
Order By: Relevance
“…MACF1 deficiency restrains the translocation of the Axin complex, which results in the disruption of the Wnt‐signaling pathways. MACF1 exhibits a phosphorylation site for GSK‐3β and also regulates GSK‐3 signaling pathway . These conclusions confirm the role of MACF1 in cell signaling and vesicular transport.…”
Section: Physiological Role Of Microtubule Actin Cross‐linking Factorsupporting
confidence: 75%
See 1 more Smart Citation
“…MACF1 deficiency restrains the translocation of the Axin complex, which results in the disruption of the Wnt‐signaling pathways. MACF1 exhibits a phosphorylation site for GSK‐3β and also regulates GSK‐3 signaling pathway . These conclusions confirm the role of MACF1 in cell signaling and vesicular transport.…”
Section: Physiological Role Of Microtubule Actin Cross‐linking Factorsupporting
confidence: 75%
“…MACF1 exhibits a phosphorylation site for GSK-3b (19) and also regulates GSK-3 signaling pathway. (28,29) These conclusions confirm the role of MACF1 in cell signaling and vesicular transport. In the case of Axonal vesicle transportation, MACF1 plays a critical role in translocation of vesicles between the Trans-Golgi network and Kif5A.…”
supporting
confidence: 71%
“…Our previous study found that MACF1 had important regulatory effects on the function of osteoblast by promoting nuclear translocation of β‐catenin, which is essential for osteogenic differentiation (Hu et al, ; Y. Zhang et al, ). We supposed that MACF1 probably regulate osteogenic differentiation through epigenetic or nonepigenetic signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Microtubule‐actin crosslinking factor 1 (MACF1) was a cytoskeletal protein regulating cellular signal transduction, proliferation, migration, and intracellular material transportation (Fassett et al, ; Hu et al, ; Kodama, Karakesisoglou, Wong, Vaezi, & Fuchs, ; X. Wang et al, ; Yue et al, ). Our previous studies have shown that MACF1 positively regulated osteoblast differentiation and osteogenic signaling pathways (Hu et al, ; Yin et al, ; Y. Zhang et al, ). We assume that MACF1 may regulate osteoblast differentiation through a series of classical or epigenetic mechanisms.…”
Section: Introductionmentioning
confidence: 98%
“…However, the downstream molecular mechanisms for the MACF1 effect in regulating osteoblast proliferation remain unclear. Previously, MACF1 was shown to participate in Wnt/β‐catenin pathway allowing β‐catenin to dissociate from the β‐catenin/AXIN/APC complex and thus transport to cell nucleus (Chen et al, ; Hu et al, ). Here, we found that the expression levels of β‐catenin increased in MACF1‐overexpression MC3T3‐E1 cells, but decreased in MACF1‐knockdown MC3T3‐E1 cells.…”
Section: Discussionmentioning
confidence: 99%